Expression and Clinical Significance of HKII and HIF-1α in Grade Groups of Prostate Cancer - Sun, Xueqi; Huang, Qirui; Peng, Fang; Wang, Jian; Zhao, Weidong; Guo, Guangxiu (Frontiers in Genetics, 2021)
Prostate cancer (PCA) is the second leading cause of cancer-related mortality in men. The glycolytic enzymes hexokinaseⅡ (HKⅡ) and the major regulator hypoxia-inducible factor-1α (HIF-1α) are PCA-specific biomarkers. Some studies have shown that HKⅡ and HIF-1α are highly expressed in PCA and are associated with the growth and metastasis of treatment. Whether HKⅡ and HIF-1α regulate the different differentiation of PCA remains largely unknown. Therefore, the study aims to explore the value of HKⅡ and HIF-1α in different grade groups of PCA. Our data indicated that compared with normal prostate tissues, the level of mRNA and protein of HKⅡ and HIF-1α in PCA increased significantly, besides the results showed the high expression of HKⅡ and HIF-1α had a tendency to promote the progression and differentiation of PCA. The study also found that HKⅡ expression was positively correlated with the expression of HIF-1α. HKⅡ and HIF-1α were related to the degree of differentiation PCA, especially in high-grade PCA. Furthermore, the high expression of HKⅡ was significantly associated with Gleason score and histological differentiation in clinicopathological characteristics of patients with PCA. These results were further used to confirm that the expression of HKⅡ and HIF-1α was associated with the progression and differentiation of PCA. These experiments indicated that HKⅡ and HIF-1α might be novel biomarkers of PCA with potential clinical application value, provide a new potential target for PCA treatment, and are expected to be used for individualized treatment in patients with PCA.